New species of Ptychozoon (Sauria: Gekkonidae) from the Nicobar Archipelago, Indian Ocean - Das, Indraneil; Vijayakumar, S. P. (Zootaxa, 2009)
A new species of Ptychozoon is described from the central portion of the Nicobar Archipelago, Bay of Bengal, India. It has been formerly referred to P. kuhli, a species widely distributed in Sundaland. Ptychozoon nicobarensis sp. nov. reaches an SVL of 100.3 mm, and is diagnosable from congeneric species in showing the following combination of characters: dorsum with a tan vertebral stripe, lacking dark transverse bars; supranasals in contact; cutaneous expansions on sides of head; absence of predigital notch in preantebrachial cutaneous expansion; imbricate parachute support scales; four irregular rows of low, rounded enlarged scales on dorsum; 20–29 scales across widest portion of tail terminus; three indistinct chevrons on dorsum; 7–11 pairs of preanal pores; femoral pores absent; tail with an expanded terminal flap and weak lobe fusion at proximal border of tail terminus. The curious distribution of the new species, centred around the central Nicobars is speculated to be the result of competition with and/or predation by large gekkonid species, to the north (Gekko verreauxi) and south (G. smithii) of the group of islands occupied by the new Ptychozoon from the central Nicobars.